MORPHOPHYSIOLOGY AND YIELD OF LATE SEASON MAIZE INTERCROPPED WITH Urochloa IN REDUCED ROW SPACING - LUIZ NETO NETO, ANTONIO; SILVA, JUSLEI FIGUEIREDO DA; DOS SANTOS, ADRIANO; PADILHA, NERIANE DE SOUZA; MAKINO, PRISCILA AKEMI; CECCON, GESSI (International Journal of Maize & Sorghum, 2014)
<!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> The aim of this study was to evaluate the morphological changes and late season maize yield in two plant densities intercropped with five populations of Urochloa (syn. Brachiaria) brizantha cv. ‘Marandu’ in reduced row spacing for pasture formation. The experiment was established on March 1, 2012 in an Oxisol in Dourados, Mato Grosso do Sul State, Brazil. A randomized block experimental design was used with split-plots in four replications. The main plot consisted of two maize plant densities (5.2 and 5.7 plants m-2) and the subplots of five plant densities of the Urochloa (0, 5, 10, 20 and 40 plants m-2). The greatest plant density of maize showed a greater leaf area index and greater yield of late season maize, but did not affect the chlorophyll content of maize and the dry matter of Urochloa. Urochloa plant densities did not affect maize yield; however, densities greater than 20 plants m-2 reduced tillering and led to increased dry matter in Urochloa. The late season maize at higher plant densities intercropped with 20 plants m-2 of U. brizantha cv. ‘Marandu’ leads to total forage dry matter production and increased maize grain yield and forage for pasture formation.